Basic VLSI design : - Pucknell, Douglas A. (Prentice-Hall, 1985)
A review of microelectronics and an introduction to nMOS technology, basic electrical properties of nMOS circuits, nMOS circuit design processes, basic circuit concepts, subsystem design and layout, scaling of nMOS circuits, PLAs and finite state machine, aspects of system design, further consideration and illustration of the design process, memory and registers and aspects of system timing, practical realities and ground rules, the real world of VLSI design